(untitled) (Journal of Oriental Studies, 2016)
In Kazakhstan, up to the present has not been carried out yet a special tudyofthecategory facilities of transmission of amount in the Chinese and Russian languages. There are many controversial issues between all articles and textbooks for high schools, exploring this question. That’s why this theme requires a full comprehensive study. The article discusses the theoretical aspects, such as the definition of the pragmatic, the value of numbers, etc.